(untitled) (Comprehensive Journal of Science, 2026)
This research presents a thermodynamic evaluation of a combined trigeneration system driven by geothermal resources. The configuration integrates a double-flash geothermal power plant with a lithium bromide water (LiBr/H₂O) absorption refrigeration system, enabling the simultaneous production of electricity heat and cooling. First- and second-law analyses were performed using the Engineering Equation Solver (EES) to characterize system behavior. The system achieved an absorption refrigeration coefficient of performance (COP) of 0.6849 an overall energy efficiency of 16.49%, and an exergy efficiency of 30.85% . The findings demonstrate the technical feasibility of exploiting geothermal energy for multi output production and highlight areas with high exergy destruction where performance enhancement is needed.